Energetics of canoe sprint kayaking - Nakagaki, K. (Japan Journal of Physical Education, Health and Sport Sciences, 2023)
The purposes of this study were 1) to estimate the metabolic energy/power of canoe sprint kayaking in terms of both accumulated oxygen deficit (AOD) and calculated energy production (AnAL+L), 2) to quantify anaerobic and aerobic metabolism during 120 s of all-out paddling and to determine the validity of the estimates calculated from the theoretical model equations, 3) to calculate propulsive efficiency (Eta) from the relationship between mechanical power and propulsive power based on kayak ergometer tests and a 500-m time trial test on the water, 4) to calculate the energy cost of kayaking (CK) and to determine the effects of Eta and body weight on CK, and 5) to simulate the metabolic power, mechanical power and propulsive power required to achieve the boat speed of an elite canoe sprint paddler. Both the AOD and AnAL+L approaches demonstrated a significant regression between mechanical power and metabolic power. Anaerobic and aerobic metabolism estimated from the model equations during 120 s of all-out paddling were not significantly different from the measured values. The Eta was 77.7±5.6%, showing a significant positive correlation with the average boat speed in the 500-m trial. The CK per body weight at any given speed was lower for kayakers with a greater body weight when Eta was a predetermined value. Based on these parameters, the present study was able to determine the required level of energy system fitness and technique for canoe sprint kayakers.